2019
DOI: 10.1159/000497438
|View full text |Cite
|
Sign up to set email alerts
|

Mucoepidermoid Carcinoma of the Parotid: Very Close Margins and Adjuvant Radiotherapy

Abstract: Background/Aims: The importance of adjuvant radiotherapy in patients with close margin resections for mucoepidermoid carcinoma of the parotid gland remains unclear. Methods: Patients who underwent parotidectomy for mucoepidermoid carcinoma with or without adjuvant radiotherapy at a single academic tertiary care center from 2000 to 2014 were identified. Included patients had negative but close (≤2 mm) surgical margins without other high-risk histopathological factors including advanced T-stage, positive nodal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…Despite this, early-stage low-and intermediategrade parotid cancers have been shown to have excellent disease control when managed with complete surgical resection, even with narrow surgical margins, in the absence of adverse features such as perineural or lymphovascular invasion or pathologic nodal disease. [319][320][321][322] Zenga et al 321 demonstrated a 100% locoregional control at a mean follow-up of 74 months in a series of 15 patients with T1-2N0 low-or intermediate-grade mucoepidermoid cancer managed with surgery alone, despite a surgical margin of # 2 mm. Similarly, in a series of 18 patients with early-stage acinic cell carcinomas of the parotid gland without adverse features (pathologic nodal disease, lymphovascular or perineural invasion, or high-grade histology), only one patient experienced a recurrence with a median follow-up of 64 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, early-stage low-and intermediategrade parotid cancers have been shown to have excellent disease control when managed with complete surgical resection, even with narrow surgical margins, in the absence of adverse features such as perineural or lymphovascular invasion or pathologic nodal disease. [319][320][321][322] Zenga et al 321 demonstrated a 100% locoregional control at a mean follow-up of 74 months in a series of 15 patients with T1-2N0 low-or intermediate-grade mucoepidermoid cancer managed with surgery alone, despite a surgical margin of # 2 mm. Similarly, in a series of 18 patients with early-stage acinic cell carcinomas of the parotid gland without adverse features (pathologic nodal disease, lymphovascular or perineural invasion, or high-grade histology), only one patient experienced a recurrence with a median follow-up of 64 months.…”
Section: Resultsmentioning
confidence: 99%
“…In earlystage low-and intermediate-grade parotid cancers, complete surgical resection with close margins has been shown to result in excellent disease control, supporting the concept of facial nerve preservation in these patients. [319][320][321][322] For advanced and high-grade tumors, it is less clear. In a retrospective series of 107 patients undergoing parotidectomy for parotid cancer, Guntinas-Lichius et al 131 used the following criteria for nerve resection: preoperative nerve weakness confirmed by electromyography believed to be related to the tumor or intraoperative suspicion of tumor infiltration of the nerve.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, radiotherapy was applied in P-MEC patients with high grade, advanced stage, and unresectable and recurrent tumors. Nevertheless, radiotherapy may result in fatigue and pain, ototoxicity, xerostomia, radiation fibrosis, and radiation-induced malignancy (Chen et al, 2013; Brusic et al, 2012; Zenga et al, 2019). Zenga et al (2019) reported that P-MEC patients with negative but close (≤2 mm) surgical margins without other high-risk histopathological factors did not benefit from adjuvant radiation in terms of long-term locoregional control.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, surgical resection remains the mainstay treatment for AciCC of the parotid gland (PG), and patients with lowgrade, early T stage (T1/T2) disease, without high-risk clinicopathological features, can be managed using surgery alone. [15][16][17][18] Zenga et al…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Due to its rarity, previous studies of AciCC in children and adolescents have predominately been reported as case series, 10-14 and it is challenging to develop a consensus on its management.According to the literature, surgical resection remains the mainstay treatment for AciCC of the parotid gland (PG), and patients with lowgrade, early T stage (T1/T2) disease, without high-risk clinicopathological features, can be managed using surgery alone. [15][16][17][18] Zenga et alreported that, if the only risk factor was close (≤ 1 mm) margins, AciCC…”
mentioning
confidence: 99%